91.0k views
1 vote
Solve using substitution. x + 3y = -13


5x + 7y = -9

User Terelle
by
6.5k points

2 Answers

3 votes
x+3y=-13
x=-3y-13
5(-3y-13) +7y = -9
-15y -65 +7y = -9
-8y-65=-9
65 -
-----
-74
/-8
------
y= 9.25

x+3(9.25) = -13
x+27.75= -13
27.75-
-------
x= -40.75

User Aandis
by
5.9k points
5 votes
Just add -3y to both of the sides:

x + 3y + -3y = -13 + -3y

x = -3y - 13

Our Answer:

x = -3y - 13
_______________________________________________________

Add -7y to both of the sides.

5x + 7y + -7y = -9 + -7y

5x = -7y - 9

Then, divide both by 5.

5x
___ = -7y - 9
5 _____
5



Our Answer: 5x
___ = - 7y -9
5 _____
5

_________________________________________________________

Hope This Helps!!!
User Abhijeet Kushe
by
6.0k points